Generalized Pathway Fractional Integral Formulas Involving Extended Multi-Index Mittag-Leffler Function in Kernel of SUM Transform - Enes Ata; Muhammad Kaurangini; Umar Muhammad Abubakar (MANAS: Journal of Engineering, 2025)
The generalized pathway fractional integral formulas for the newly extended multiindex Mittag-Leffler function defined by using two Fox-Wright functions as its kernel is studied. Moreover, the SUM integral transform of the composition formula for the pathway fractional integral and extended multi-index Mittag-Leffler function is also presented.